A genome-wide siRNA screen reveals multiple mTORC1 independent signaling pathways regulating autophagy under normal nutritional conditions - Lipinski, Marta M. (2010)
Autophagy is a cellular catabolic mechanism that plays an essential function in protecting multicellular eukaryotes from neurodegeneration, cancer and other diseases. However, we still know very little about mechanisms regulating autophagy under normal homeostatic conditions when nutrients are not limiting. In a genome-wide human siRNA screen, we demonstrate that under normal nutrient conditions up regulation of autophagy requires the type III PI3 kinase, but not inhibition of mTORC1, the essential negative regulator of starvation-induced autophagy. We show that a group of growth factors and cytokines inhibit the type III PI3 kinase through multiple pathways, including the MAPK-ERK1/2, Stat3, Akt/Foxo3 and CXCR4/GPCR, which are all known to positively regulate cell growth and proliferation. Our study suggests that the type III PI3 kinase integrates diverse signals to regulate cellular levels of autophagy, and that autophagy and cell proliferation may represent two alternative cell fates that are regulated in a mutually exclusive manner.